Dynamics on the Boston Consulting Group's planning matrices - C. G. Robinson (South African Journal of Business Management, 1985)
Strategies based on the growth share matrix as a resource allocation tool require that broad categories of businesses are either funded, milked, or divested depending on their strategic positioning on the portfolio chart. Dynamics on the chart are important and this article explores the implications of changing positions of the businesses concerned using the growth gain matrix. The little-used technique of frontier curves, which relates growth rate to cash usage, is elucidated. Because management cannot act in a vacuum and competitive action is inevitable, a checklist for competitive profiling is provided. Competitive dynamics on the growth share matrix are explored least the unwary fall into the trap of conventional strategic thinking.
Keywords: 650